COMMUNICATION SKILLS: FACILITATING STUDENTS’ INVISIBLE BUT SIGNIFICANT SKILLS TO IMPROVE HEALTH OUTCOMES - Hikmawati Nurrokhmanti,; Astrid Pratidina Susilo; Rosaria Indah; Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia, 2022)
Background: Communication skills are the core skills throughout medical professional life and embedded with cultural factors. Although students have learned communication skills in the undergraduate education, adequate training during clinical rotation and continuing professional development is necessary. Facilitating the students to build partnership relationship in the communicating with patients is challenging, considering its contexts, facilities, and opportunities. The influence of student-teacher relations in this hierarchical context is also influential.